Modeling and Analysis of Clinical & Municipal Waste Incineration Process using Aspen Plus - Mohamad Rizza, Othman; Anpalagam, Sivanesh Kumar; Nur Fitriyanni, Jafary (Elsevier B.V., 2023)
Modeling and analyzing the solid waste incineration process is a salient study for future advanced waste disposal technology and optimizing process efficiency. However, the development of a mechanistic model that describes the process deal with several challenges and has yet to be extensively explored. Thus, this paper aims to develop a mechanistic model for clinical and municipal solid waste incineration in Aspen Plus. The waste was modeled using customized non-conventional (NC) solid properties, and a general coal enthalpy model with heat correlations to calculate the heating value. The model results accurately depict the waste heating values found in the literature. Further analysis reveals the ability of the model to describe the effect of waste feed quality on incinerator performance.